Employability skills and self-perception of diploma 3 graduates in the world of work - Rina Febriana; Ivan Hanafi; Annis Kandriasari; Apri Nuryanto; Soeprijanto Soeprijanto; Muksin Muksin; Su Jo Ching; Abu Bakar Mamat (Jurnal Pendidikan Vokasi, 2023)
This study aims to determine the world's perception of Diploma 3 graduates regarding work skills. The research used a questionnaire survey method on Diploma 3 graduates who had worked for 2-5 years. Measurement of work aspects includes individual qualities, basic skills, interpersonal skills, thinking skills, resource management, systems and technology, and information skills. The instrument's validity in each aspect ranges from 0.416 to 0.683, with a reliability of 0.882. The research technique used simple random sampling with 109 respondents in this study. The results of the study stated that the self-perception of graduates are (1) an individual quality score of 85.5 with a very high interpretation; (2) basic skills get a score of 81.8 with a high interpretation; (3) an interpersonal score of 84.8 with a very high interpretation; (4) thinking skills get a score of 83.1 with a very high interpretation; (5) resource management obtained a score of 88.6 with a very high interpretation; (6) systems and technology got a score of 92.4 with a very high interpretation, and (7) information skills got a score of 85.1 with a very high interpretation. Thus, the average worldwide employment of Diploma 3 graduates is 85.9, with a high interpretation. This finding implies that the higher graduates' employability skills, the higher their self-perception at work.